Dialektika Receptio In Complexu dan Receptio A Contrario: Implementasi Hukum Islam Dalam Sistem Hukum Indonesia - Miftahul Jannah,; Kurniati Kurniati,; Musyfikah Ilyas, (Tasamuh: Jurnal Studi Islam, 2025)
The implementation of Islamic law in the Indonesian legal system is a complex issue involving the interaction between religious authorities, the state, and society. This research aims to analyze the dialectic between the theories of Receptio in Complexu (Islamic law applies automatically to Muslims) and Receptio a Contrario (Islamic law applies as long as it does not contradict custom) and its impact on the integration of Islamic law in the national legal framework. The research method used is library research with a theological-normative approach and contextual analysis, combining primary (legal texts, colonial documents) and secondary (journals, books) data. The results show that inconsistencies in the application of Islamic law, such as in the case of Bugis customary inheritance which contradicts the provisions of faraidh, reflect the tug-of-war between religious, customary and state authorities. The implications include legal uncertainty, regulatory dualism, and the potential for social disharmony. Islamic legal products such as the Compilation of Islamic Law (KHI) and MUI fatwas have been recognized, but their application remains influenced by the socio-cultural context. To create harmonious integration, a benefit-based approach (istislahi), regulatory harmonization, and the active role of Islamic organizations and community leaders are needed. This research provides academic and practical recommendations to strengthen an inclusive national legal system, and encourages further research on the integration model of Islamic law based on maqashid sharia and local wisdom within the framework of Pancasila.